Jogo Sério Para A Consciencialização E Prevenção De Esquemas Fraudulentos De Romance - Nuno Filipe da Silva Freitas (2022)
The concept of "serious games" has been the subject of academic interest due to the possibility of video games helping to teach skills and knowledge applicable to various areas, in a more effective and attractive way than traditional means of education. However, its application in cybersecurity appears to lack depth and there are several issues within the area that affect the general population, for which no serious games proposals were found. Considering the aforementioned context, this dissertation arose to develop and propose a concept for a serious game involving a common cybersecurity problem: romance scams, in which some dating app users become targets of financial and emotional fraud by finding themselves involved in a fake relationship, created by the criminals involved in the scams. In the game concept achieved within this dissertation, the player takes the role of a moderator for a fictional dating app, tasked with responding correctly to a queue of reports concerning possible romance scams. Similar to a point-and-click game, the player must analyze each report and their included data about the users in question and their activity, using the available in-game tools, and subsequently make a decision about whether each report is valid or invalid. The process hereby registered involved the distribution of a questionnaire to ascertain the knowledge and interests of a sample of the population, the subsequent prototyping of one game concept achieved from the results of the questionnaire and its validation through game testing with a sample of the population, accompanied by a second evaluation questionnaire.